Fertility Preservation: A Key Survivorship Issue for Young Women with Cancer - Angarita, Ana Milena; Johnson, Cynae A.; Fader, Amanda Nickles; Christianson, Mindy S. (Frontiers in Oncology, 2016)
Fertility preservation in the young cancer survivor is recognized as a key survivorship issue by the American Society of Clinical Oncology and the American Society of Reproductive Medicine. Thus, health care providers should inform women about the effects of cancer therapy on fertility and should discuss the different fertility preservation options available. It is also recommended to refer women expeditiously to a fertility specialist in order to improve counseling. Women’s age, diagnosis, presence of male partner, time available and preferences regarding use of donor sperm influence the selection of the appropriate fertility preservation option. Embryo and oocyte cryopreservation are the standard techniques used while ovarian tissue cryopreservation is new, yet promising. Despite the importance of fertility preservation for cancer survivors’ quality of life, there are still communication and financial barriers faced by women who wish to pursue fertility preservation.